TALENT MANAGEMENT PRACTICES WITH REFERENCE TO TALENT RETENTION IN INDIA - Sundarapandiyan, N.; Sundarapandiyan, N.; Babu, S. (International Journal For Research In Business, Management And Accounting, 2017)
An organisational strategic plan defines an organisational direction and leads to an effective talent management planning. Planning of talents for the future of an organisation is not a onetime activity; it is a systematic continuous process. Talent Management includes Talent Attraction and Sourcing, Talent Development, Talent Retention and Succession Planning of an organisation. Organisational assessment brings out the gap between where the organisation is now and where it is expected to be in the future. This involves analysing the organisation’s strength, weakness, opportunity and threat and prioritising the corporate vision, mission and values. Based on this, there is a requirement to put in plan and map the talent requirements of today and finding future stars is the responsibility of corporate leaders in transforming the organisation’s success. This paper focuses on the Talent Management issues faced by corporates today and analysis of various possible practices to overcome the challenges for their organisational strategic transformation. This paper also suggests incorporating Talent Management in higher education courses to coach and develop and enhance the potential graduate’s competencies to meet the future organizational needs.